Individual risk factors associated with general unintentional injuries and the relationship to traumatic dental injuries among children aged 0–15 years in the Swedish BITA study. Issue 4 (22nd January 2016) - Oldin, Anna; Lundgren, Jesper; Norén, Jörgen G.; Robertson, Agneta
Abstract: Aim: To investigate general unintentional injuries (GUI) and traumatic dental injuries (TDI) in relation to behavioral and psychosocial strengths and difficulties among Swedish children aged 0–17 years, and to investigate general unintentional injuries in relation to temperament and socioeconomic status among the same children. Subjects and methods: The study included 2363 children in four different age cohorts aged 3, 7, 11, and 15 years at the study start. Twelve Public Dental Service clinics in Sweden participated, representing different types of demographic areas, both rural and urban. Data were collected from parents and children through an interview, questionnaires, and dental records. Results: Twenty‐four percentage (24%) of the children had experienced a serious general unintentional injury (GUI) at some point during their lifetime up until 3 months prior to the study start. Children who were regarded by their parents as being injured more often than other children also had occasions with general unintentional injuries to a greater extent. Most general unintentional injuries occurred at home. Children with incidents of general unintentional injuries had occasions with TDI to a greater extent than children without general unintentional injury. Children, whose mothers had 11 years of school/education or less, were involved in more general unintentional injuries during the 3‐month period prior to the study start, compared to children of mothers with higher education level. Conclusions: Children with general unintentional injuries had more traumatic dental injuries. Children who were assessed by their parents as being injured more often than other children also had occasions with general unintentional injuries to a greater extent. Temperament, behavioral and psychosocial strengths and difficulties had different impacts at different ages for experiencing a general unintentional injury.